INTERDISCIPLINARITY IN HEALTH: THE MEDICAL HUMANITIES - Nascimento, Rafael Verneck do; Figueiredo, Rodrigo Cruvinel; de Abreu Quintela, Mirelle Cristina; Bastos Cacciari, Marcella; de Abreu Quintela Castro, Fernanda Cristina; Mota Braga Chiepe, Kelly Cristina; Bellettini dos Santos, Tatiani; Morandi de Assis Lemos, Clécio José (UNESC em Revista, 2025)
Studies in the philosophy of science indicate that the major innovations of recent decades are due to interdisciplinarity. This article addresses the growing relevance of interdisciplinarity in the health field and how it represents a significant change in relation to the traditional paradigm of disciplines. This highlights the need to overcome excessive specialization, which has fragmented knowledge across various disciplines and hindered an in-depth understanding of current challenges. This text exemplifies new areas of investigation that arise from the connection with human sciences and applied social sciences, which can be framed in the new field of the medical humanities. Keywords: Humanities. Medical. Health. Interdisciplinarity. Science.